Antibacterial oleanane-type triterpenoids from pericarps of Akebia trifoliata. (1st February 2015) - Wang, Jing; Ren, Hui; Xu, Qiao-Lin; Zhou, Zhong-Yu; Wu, Ping; Wei, Xiao-Yi; Cao, Yong; Chen, Xue-Xiang; Tan, Jian-Wen
Highlights: Three new (1 −3 ) and 10 known oleanane triterpenoids were isolated from pericarps of Akebia trifoliata . Their structures were identified by spectroscopic analysis. Antibacterial activity was evaluated against two Gram-(+) and three Gram-(−) bacteria. Compounds4, 6 and11 showed significant in vitro antibacterial activity toward all the test bacteria strains. Abstract: Three new oleanane triterpenoids, 2 α, 3 β, 29-trihydroxyolean-12-en-28-oic acid (1 ), 2 α, 3 β -dihydroxy-23-oxo-olean-12-en-28-oic acid (2 ) and 2 α, 3 β, 21 β, 22 α -tetrahydroxyolean-12-en-28, 29-dioic acid (3 ), and ten known ones, maslinic acid (4 ), arjunolic acid (5 ), oleanolic acid (6 ), 3- epi -oleanolic acid (7 ), stachlic acid A (8 ), serratagenic acid (9 ), gypsogenic acid (10 ), 2 α, 3 β -dihydroxyol-ean-13(18)-en-28-oic acid (11 ), mesembryanthemoidigenic acid (12 ) and 12 α -hydroxy-δ-lactone (13 ), were isolated from the pericarps of Akebia trifoliata, a new valued fruit crop in China. Their structures were elucidated on the basis of extensive spectroscopic analysis. Compounds8, 10, 11 and13 were isolated for the first time from the genus Akebia . All the compounds were tested for their antimicrobial activity against five bacterial strains. Compounds4, 6 and11 showed significant antibacterial activity toward all the assayed microorganisms with MIC values ranging from 0.9 to 15.6 μg/mL, which were close or even more potent than the reference compound Kanamycin (MIC values ranging from 1.9 to 3.9 μg/mL).